Effect of fines on strength and durability of concrete with manufactured sand. (2022) - Praveen Kumar, K.; Radhakrishna,; Ramesh, P.S.; Aravinda, P.T.
Abstract: Presently Manufactured sand is widely used as an alternative to natural sand in cement composites due to restrictions laid by authorities on extraction of sand from river and non-availability of good quality natural sand. This study includes investigation of the properties of M-sand concrete with varying percentage of fines. Concrete of M55 grade was designed with M-sand as fine aggregate. Percentage of particles having size <150 µ (fines) was varied from 0 to 20% with an interval of 5. Constant workability of 90–110 mm slump was maintained at each replacement level by varying dosage of superplasticizer. Concrete cubes, cylinders and beams were cast and cured for 28 days. Compressive, split tensile, flexural and shear strength were found apart from evaluation of variation of density, water absorption, sorptivity and permeability of concrete. Microstructure of concrete with different percentages of fines were studied. It was concluded that workability of fresh concrete and density increases with increase in fines. M-sand concrete with 5% fines exhibits optimum strength and durability properties with presence of dense CSH Gel and lesser number of pores. However, from strength consideration, upto 15% replacement of fine aggregates by fines can be recommended.